2017
DOI: 10.1101/163758
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural covariance networks are coupled to expression of genes enriched in supragranular layers of the human cortex

Abstract: Complex network topology is characteristic of many biological systems, including anatomical and functional brain networks (connectomes). Here, we first constructed a structural covariance network (SCN) from MRI measures of cortical thickness on 296 healthy volunteers, aged 14-24 years. Next, we designed a new algorithm for matching sample locations from the Allen Brain Atlas to the nodes of the SCN. Subsequently we use this to define, transcriptomic brain networks (TBN) by estimating gene co-expression between… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
102
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(105 citation statements)
references
References 54 publications
3
102
0
Order By: Relevance
“…We used the AHBA transcriptomic dataset, with gene expression measurements in 6 postmortem adult brains (45) (http://human.brain-map.org), aged 24-57. Each tissue sample was assigned to an anatomical structure using the AHBA MRI data for each donor (46). Samples were pooled between bilaterally homologous cortical areas.…”
Section: Methodsmentioning
confidence: 99%
“…We used the AHBA transcriptomic dataset, with gene expression measurements in 6 postmortem adult brains (45) (http://human.brain-map.org), aged 24-57. Each tissue sample was assigned to an anatomical structure using the AHBA MRI data for each donor (46). Samples were pooled between bilaterally homologous cortical areas.…”
Section: Methodsmentioning
confidence: 99%
“…We generated a 308-region (n=152 LH regions) cortical parcellation using a backtracking algorithm to restrict the parcel size to be approximately 500mm 2 , with the Desikan-Killiany atlas boundaries as starting points 50,51 . This parcellation has been used in previous structural 19,52,53 and functional 20 imaging studies of connectomes, and was also used in our first study of MSNs 16 .…”
Section: Cortical Parcellationmentioning
confidence: 99%
“…Methods for the alignment of the microarray gene expression data from 6 adult human donors, provided by the Allen Human Brain Atlas (AHBA), to the left hemisphere (n = 152 regions) of our parcellation has been described in depth elsewhere 8,16,52 , where we have shown that the gene expression data is robust to leaving a given donor out of the analysis. Briefly, we used FreeSurfer's recon-all to reconstruct and parcellate the cerebral cortex of each AHBA donor using the corresponding T1-weighted volume 56 .…”
Section: Transcriptomic Alignment Of Neuroimaging Datamentioning
confidence: 99%
“…MRI images of the AHBA donors were parcellated using the Desikan-Killiany atlas and each cortical tissue sample was assigned to an anatomical structure. Regional expression levels were compiled to form a (68 × 20,647) regional transcription matrix (38); see SI.…”
Section: Estimation Of Regional Gene Expressionmentioning
confidence: 99%